1952
DOI: 10.1182/blood.v7.4.417.417
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cellular Composition of the Lymph Caused by Ionizing Radiations

Abstract: Erythrocytes appear in large numbers in the lymph of rats and dogs after massive exposure to x rays. The peak of endothelial fragility, as indicated by the erythrocyte counts in the lymph, is reached on the ninth to fourteenth day in rats and the eleventh to seventeenth day in dogs. In both species the erythrocyte count in the lymph frequently exceeds one million. Diversion of erythrocytes into the lymph compartment causes a relative anemia; excessive destruction of erythrocytes, presumably rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1952
1952
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The appearance of atypical mononuclear cells during recovery after irradiation has been reported in various species including man (Benjamin, v. Reuss, Sluka and Schwarz, 1906;Wiinshe, 1938;Bauer, 1940;Denstad, 1943 ;Brecher, Endicott, Gump and Brawner, 1948;Ross, Furth and Bigelow, 1952;Schlumberger and Vasquez, 1954;Oughterson and Warren, 1956;Harris, 1956). The cells have been described either as atypical lymphocytes or atypical monocytes but those seen during the present investigation were more like lymphocytes than monocytes.…”
Section: Lymphocyte Morphology During Recoverymentioning
confidence: 83%
“…The appearance of atypical mononuclear cells during recovery after irradiation has been reported in various species including man (Benjamin, v. Reuss, Sluka and Schwarz, 1906;Wiinshe, 1938;Bauer, 1940;Denstad, 1943 ;Brecher, Endicott, Gump and Brawner, 1948;Ross, Furth and Bigelow, 1952;Schlumberger and Vasquez, 1954;Oughterson and Warren, 1956;Harris, 1956). The cells have been described either as atypical lymphocytes or atypical monocytes but those seen during the present investigation were more like lymphocytes than monocytes.…”
Section: Lymphocyte Morphology During Recoverymentioning
confidence: 83%
“…These vascular defects mostly consisted of abnormal connections between blood and lymphatic vessels resulting in the development of blood‐filled lymph sacs and lymphatic vessels, and in impaired lymphatic drainage evidenced by the presence of cutaneous and intestinal oedema in neonatal animals. Interestingly, early studies have shown abnormal red blood cell accumulation within the lymph of animals rendered thrombocytopenic by irradiation [10,49–51]. Although entry of red blood cells in the lymph of irradiated animals occurred even in the absence of evidence of a haemorrhagic tendency [50], it was interpreted as an indicator of the degree of irradiation‐induced capillary damage and erythrodiapedesis.…”
Section: Platelets Support Vascular Development and Remodellingmentioning
confidence: 99%
“…9 The leukocyte count in the thoracic duct in healthy men varies from 2 to 20 Â 10 9 and consists almost totally of lymphocytes (i.e., nearly 2 to 10 times the number of lymphocytes that can be found in the peripheral blood), whereas the number of erythrocytes is negligible under physiological conditions, but might increase remarkably in certain disorders characterized by marked capillary damage and extravasation. 10,11 The fluid, the macromolecules, and the cells are transported to the lymph node system and then-through the lymph vessels-to the right and left thoracic ducts, before being reversed into the right or the left subclavian vein, where the lymph is finally mixed with the blood.…”
Section: Biology and Function Of The Lymphatic Systemmentioning
confidence: 99%